Effects of intermittent exercise on cardiac troponin I and creatine kinase-MB - Nader Rahnama; Mohammad Faramarzi; Abass Ali Gaeini (International Journal of Preventive Medicine, 2011)
Objectives: The aim of this study was to examine the influence of high-intensity intermittent exercise and carbohydrate supplementation on cardiac troponin I (cTnI) and creatine kinase-MB (CK-MB) in soc-cer players. Methods: Twelve elite soccer players were selected and divided equally into three groups of carbohydrate (CHO), placebo (P) and control (C). Blood samples were taken in six phases and were analyzed with the chemiluminescence method. Results: Results showed that three bouts of 90-min exercise along with carbohydrate supplementation did not have any significant effect on the level of cTnI indices. However, there was a significant differ-ence in CK-MB values after the second and third sessions compared with the first day (P < 0.05). Conclusion: In summary, exercises with less duration and intensity like soccer do not seem to be effective on cTnI and CK-MB. When the overall intensity of exercise was moderate, it appeared that carbohy-drate supplementation had less effect on the alteration of biochemical markers of the myocardial muscle.